(untitled) (Ius Novum, 2024)
With the adoption of the acquis communautaire, the Polish administration encountered a significant number of soft law acts issued by the EU administration and began to utilise them extensively. The systematic ‘hardening’ of soft law acts leads to a discrepancy between their formally non-binding status and their actual intended meaning and effects – often resembling ‘hidden directives’ or even more imperative measures, producing legal consequences and defining the legal situation of e.g. entrepreneurs. Consequently, it is proposed that soft law acts should be subject to autonomous judicial review in terms of both interpretation and annulment. The President of UOKiK may also issue official explanations and guidelines that fit the definition of soft law acts. Guidelines on the amounts of fines for entrepreneurs significantly impact the determination of their legal position, and judicial decisions increasingly refer to the methodology of setting fines specified therein without critical examination.